REGARDING THE CORRECTNESS OF LEGAL FORMULATION OF ARMED FORCES OF UKRAINE FUNCTIONS - Olexander P. Duz-Kriatchenko; Anatolii A. Lobanov; Eduard M. Lysytsyn (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
In the article clarifies the issues of defence of state by the Armed Forces of Ukraine and preservation of state sovereignty.